2017
DOI: 10.3390/molecules22020222
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Oil of Monarda didyma L. (Lamiaceae) Exerts Phytotoxic Activity in Vitro against Various Weed Seed

Abstract: The chemical composition of the essential oil of the flowering aerial parts of Monarda didyma L. cultivated in central Italy was analyzed by Gas Chromatography/Mass Spectrometry (GC/MS). The major compounds of the oil were thymol (59.3%), p-cymene (10.3%), terpinolene (9.2%), δ-3-carene (4.4%), myrcene (3.7%), and camphene (3.4%). The essential oil was tested in vitro for its anti-germination activity against Papaver rhoeas L., Taraxacum officinale F. H. Wigg., Avena fatua L., Raphanus sativus L. and Lepidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 24 publications
2
21
1
1
Order By: Relevance
“…3). The growth retardatory effects of Melaleuca oil on the test plants is in agreement with earlier studies reporting inhibitory effect of volatile oils from aromatic plants on the seedling growth of weeds (Singh et al, 2009;Rolli et al, 2014, Arora et al, 2016Ricci et al, 2017). The reduction in early growth of weeds could be due to the inhibitory effect of plant volatiles on the cell division and lowered root mitotic activity, DNA synthesis of growing root tips and disruption of the membranes (Nishida et al, 2005;Ahuja et al, 2015).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3). The growth retardatory effects of Melaleuca oil on the test plants is in agreement with earlier studies reporting inhibitory effect of volatile oils from aromatic plants on the seedling growth of weeds (Singh et al, 2009;Rolli et al, 2014, Arora et al, 2016Ricci et al, 2017). The reduction in early growth of weeds could be due to the inhibitory effect of plant volatiles on the cell division and lowered root mitotic activity, DNA synthesis of growing root tips and disruption of the membranes (Nishida et al, 2005;Ahuja et al, 2015).…”
Section: Resultssupporting
confidence: 90%
“…1). The observations made in the present study are parallel to earlier studies documenting the inhibition of seed germination in response to essential oils (Singh et al, 2009;Grichi et al, 2016;Ricci et al, 2017). From the previous studies, it has been known that the essential oil exhibited potent inhibitory effect on germination and growth, and causing morphological and physiological changes in the plant seedlings (Kordali et al, 2015;Bali et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…Also, a Monarda species grown in Canada underlined thymol (41.17%), γ-terpinene (15.88%), carvacrol (15.20%), and p-myrcene (12.58%) as main constituents [115]. Two other studies published in 2017 reported the EO composition from this plant species cultivated in central Italy: the EO from the flowering aerial parts pointed to thymol (59.3%) and p-cymene (10.3%) as major compounds [116], while the second work evidenced thymol 62% [43]. Other Monarda species, always cultivated in Italy, were very rich in monoterpenes, but with o-cymene (13.42), γ-terpinene (22.15), and carvacrol (13.80%) as the main constituents, and thymol with a lesser amount (5.87%) [42].…”
Section: Essential Oilsmentioning
confidence: 85%
“…EOs inhibiting the growth of tested plants via ROS overproduction leading to oxidative stress and degradation of membrane integrity was evidenced via increased levels of MDA and EL, and decreased levels of conjugated dienes were demonstrated for other EOs such as Pogostemon benghalensis [45], Monarda didyma [46] and Artemisia scoparia [47].…”
Section: Reactive Oxygen and Nitrogen Species Inductionmentioning
confidence: 94%